THE EFFECT OF LOAN TO DEPOSIT RATIO, NET PROFIT MARGIN, COMPANY AGE, INFLATION RATE, AND BI INTEREST RATE ON RETURN ON ASSETS IN CONVENTIONAL BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2020-2024 - Jeslyn Goh; Anton Anton; Irawati Irawati; Helly Aroza Siregar; Zulhelmi Zulhelmi (Procuratio : Jurnal Ilmiah Manajemen, 2026)
This study aims to analyze the effect of the Loan to Deposit Ratio (LDR), Net Profit Margin (NPM), Company Age, Inflation Rate, and BI Interest Rate on Return on Assets (ROA) in conventional banking companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses secondary data obtained from annual financial reports and official macroeconomic data. The research sample consisted of 40 conventional banking companies selected using a purposive sampling method. Data analysis techniques were carried out using SmartPLS with a path analysis approach. The results showed that the variation of the independent variables used on the dependent variable in this study was declared feasible with the ability to explain the dependent variable, namely Return on Assets, by 64%. The results also showed that LDR had a negative and insignificant effect on ROA, NPM had a positive and significant effect on ROA, company age had a negative and significant effect on ROA, Inflation Rate had a negative and insignificant effect, and Interest Rate had a positive and insignificant effect on ROA. Penelitian ini bertujuan untuk menganalisis pengaruh Loan to Deposit Ratio (LDR), Net Profit Margin (NPM), Umur Perusahaan, Tingkat Inflasi, dan Suku Bunga BI terhadap Return on Asset (ROA) pada perusahaan perbankan konvensional yang terdaftar di Bursa Efek Indonesia periode 2020–2024. Penelitian ini menggunakan data sekunder yang diperoleh dari laporan keuangan tahunan serta data makroekonomi resmi. Sampel penelitian terdiri dari 40 perusahaan perbankan konvensional yang dipilih menggunakan metode purposive sampling. Teknik analisis data dilakukan menggunakan SmartPLS dengan pendekatan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa variasi dari variabel independen yang digunakan terhadap variabel dependen dalam penelitian ini dinyatakan layak dengan kemampuan menjelaskan variabel dependen yaitu Return on Asset  sebesar 64%. Hasil penelitian juga menghasilkan bahwa LDR berpengaruh negatif dan tidak signifikan terhadap ROA, NPM berpengaruh positif dan signifikan terhadap ROA, umur perusahaan berpengaruh negatif dan signifikan terhadap ROA, Tingkat Inflasi berpengaruh negatif dan tidak signifikan dan Suku Bunga berpengaruh positif dan tidak signifikan terhadap ROA.